2016
DOI: 10.5798/diclemedj.0921.2016.01.0640
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Cross-Linking With Riboflavin/UV-A in Patients With Progressive Keratoconus

Abstract: Objective: To evaluate the results of corneal cross-linking with UV-A/riboflavin in patients with progressive keratoconus.Methods: Forty-seven eyes of 30 patients with progressive keratoconus (16 female, 14 male) were included in the study. Uncorrected and the best corrected distance visual acuities, biomicroscopic findings, intraocular pressure measurements, fundoscopic findings, pachymetric measurements and corneal topography parameters were recorded for each patient. Results:The mean age of the patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…There are contradictory results regarding CDVA alterations after CXL treatment.Bozkurt et al reported increased CDVA after A-TE CXL, on the other hand, few reports detected no significant changes [23][24][25] . In this study, there was a significant increase in CDVA 6 months after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…There are contradictory results regarding CDVA alterations after CXL treatment.Bozkurt et al reported increased CDVA after A-TE CXL, on the other hand, few reports detected no significant changes [23][24][25] . In this study, there was a significant increase in CDVA 6 months after the procedure.…”
Section: Discussionmentioning
confidence: 99%